Spanish phrase book & dictionary. - Berlitz Publishing Company (New York : Berlitz Pub., 2007)
Meet and greet locals easily and comfortably using the Berlitz Phrase Book, the unparalleled market leader in foreign language books. Perfect for both business travelers and vacationers, this easy-to-use, color-coded reference contains essential expressions, a bilingual dictionary, and menu reader.
Keywords: Spanish language -- Conversation and phrase books -- English; Spanish language materials -- Bilingual; Spanish language; Phrase books; Dictionaries; Conversation and phrase books; Dictionaries; Phrase books